New media for increasing political participation in Indonesia - Uspal Jandevi (Association for Scientific Computing Electrical and Engineering (ASCEE), 2019)
This paper aims to corelation among The development of information and communication technology (ICT) encouraging diverse patterns of change including government and public relations in a democracy this research is a library study, a library that contains an in-depth collection of materials for one more subjects. Research libraries usually include primary and secondary sources. In the end we must realize ICT is a tool not a solution for democracy. The main lesson from countries that are able to adopt the principles of e-democracy to improve the quantity and quality of participation of its citizen is a good preparation prior to application in the field.